Daily sitting time and its association with non-communicable diseases and multimorbidity in Catalonia. (30th November 2021) - Poses-Ferrer, Elisa; Parisi, Rosa; Gonzalez-Viana, Angelina; Castell, Conxa; Arias de la Torre, Jorge; Jones, Andrew; Serra-Sutton, Vicky; Espallargues, Mireia; Cabezas, Carmen
Abstract: Background: Non-communicable diseases (NCDs) account for 71% of deaths worldwide and individual behaviours such as sedentariness play an important role on their development and management. However, the detrimental effect of daily sitting on multiple NCDs has rarely been studied. This study sought (i) to investigate the association between sitting time and main NCDs and multimorbidity in the population of Catalonia and (ii) to explore the effect of physical activity as a modifier of the associations between sitting time and health outcomes. Methods: Cross-sectional data from the 2016 National Health Survey of Catalonia were analyzed, and multivariable logistic regression, adjusting for socio-demographics and individual risk factors (tobacco and alcohol consumption, diet, hyperlipidaemia, hypertension, body mass index) was used to estimated odds ratios (ORs) and 95% confidence intervals (CIs) of the association between sitting time and NCDs. Results: A total of 3320 people ≥15 years old were included in the study. Sitting more than 5 h/day was associated with a higher risk of cardiovascular disease (OR 1.90, 95% CI: 1.21–2.97), respiratory disease (OR 1.61, 95% CI: 1.13–2.30) and multimorbidity (OR 2.80, 95% CI: 1.53–5.15). Sitting more than 3 h/day was also associated with a higher risk of multimorbidity (OR 2.26, 95% CI: 1.23–4.16). Physical activity did not modify the associations between sitting time and any of the outcomes. Conclusions: Daily sitting time might be an independent risk factor for some NCDs, such as cardiovascular disease, respiratory disease and multimorbidity, independently of the level risk of physical inactivity.